PENGARUH PEMILIHAN PRESIDEN RI TAHUN 2009 TERHADAP HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM PERUSAHAAN DI BURSA EFEK INDONESIA - Harymami, Harymami; Alkaff, Maria Qifthiyah (Journal of Accounting and Strategic Finance, 2010)
The data used in this research is secondary data from 30 companies listed in Indonesia Stock Exchange and a member of the Jakarta Islamic Index in the year 2009, which consists of daily stock price, trading volume, and the Composite Index daily for 7 days before and 7 days after the presidential election of RI. Statistical analysis used is different from two-sample test in pairs (paired sample t-test) using SPSS program. Based on the analysis of the 15 concluded that there is significance of the observation period of market reactions or abnormal stock return in the period prior to 4 (t-4, t-3, t-2, t-1) and After 2 periods (t 6, t 7) election President of Republic of Indonesia dated July 8, 2009. Also concluded that there was no significant difference in abnormal returns and trading volume between the period of 7 days prior to 7 days after the events of Indonesia's presidential election on 8 July 2009, so the hypothesis that there are significant differences in abnormal stock returns and trading volume between periods 7 days prior to 7 days after the date of Indonesia's presidential election July 8, 2009 did not prove true. Keywords: abnormal stock return, stock trading volume.